Klamath Tribal Response to the Pandemic of COVID-19 Among Klamath Tribal Community in Oregon, USA - Obinna Oleribe DrPH, FRCP, MBA; Rachel Miller BSN, RN; Misty Wadzeck RN, BSN; Nikowa Mendez BSN, MHA; Joseph Tibay MS, RDN; Timothy Langford PharmD, BCPS; Anjanette Devine DNP; Simon D Taylor-Robinson MD, FRCP, FWACP (SAGE Publishing, 2021)
Introduction Socially-disadvantaged populations are more at risk of contracting COVID-19 than those with access to better medical facilities. We looked at responses of Klamath Tribes in Oregon, USA to mitigate spread of COVID-19 in a community with a higher incidence of obesity, diabetes and coronary heart disease, compared to the general US population. This study reports on Klamath Tribes response to COVID-19 March -September 2020. Methods Klamath Tribes Tribal Health and Family Services established a COVID-19 Incident Management Team (IMT), instituting creative programs including a Walk-In Testing Center, implementing strict infection control protocols and regular sharing of information on the pandemic and prevalence of COVID-19 amongst Klamath Tribes. All COVID-19 tests were documented with positive cases isolated and people with high risk exposures quarantined and provided with wrap-around medical and social services until recovered or past quarantine time period. Results A total of 888 (12%) tribal members were tested for COVID1-19 between March to September 2020; 50 were found positive for COVID-19, giving a test positivity rate of 5.6% (Male - 6.3%; Female - 5.2%). No deaths have been reported amongst the local Klamath Tribes and other American Indians/Alaska Native (AI/AN) population served by the tribe. Conclusion Despite the fact that structural inequities including income disparities have shaped racial and ethnic impact of epidemics around the world, the timely response, establishment of partnerships and proactive control of the epidemic resulted in minimal impact among the Klamath Tribal and other AI/AN populations served by the tribal facilities.